Evaluating the cost of malaria elimination by Anopheles gambiae precision guided SIT in the Upper River region, The Gambia. - William A C Gendron; Robyn Raban; Agastya Mondal; Héctor M Sánchez C; Andrea L Smidler; David Zilberman; Patrick G C Ilboudo; Umberto D'Alessandro; John M Marshall; Omar S Akbari (PLOS Global Public Health, 2025)
Mosquito control has successfully reduced the burden of malaria globally, but current vector control technologies cannot achieve malaria elimination. Precision guided sterile insect technique (pgSIT) is one of the most promising interventions being developed for malaria elimination. Mass release of genetically sterile males can act as a chemical-free species-specific insecticide. Before translating pgSIT from the bench to the field, however, it is essential to understand the potential costs and capabilities of this technology in a malaria-endemic region to determine if further investment into research and development of this technology is worthwhile. Therefore, we estimated the health outcomes and costs of a pgSIT program working jointly with current interventions to control the Anopheles gambiae malaria vector in the Upper River region of The Gambia. The pgSIT intervention in this region is predicted to prevent approximately 230 deaths and about 48,000 sick days per year. We have provided a range of costs that include risks associated with research and development, the facility, mass rearing efficiency, and distribution. This intervention should save disability-adjusted life years (DALY) at 11-94 USD per year and will prevent cases at 10-86 USD per infection. These estimates predict that pgSIT will cost 0.36-3.03 USD per person in the treated region annually. The cost per DALY shows life-saving at a cost comparable to current interventions in the Upper River region.